Cadherin Cell Adhesion System in Canine Mammary Cancer: A Review. (22nd August 2012) - Gama, Adelina; Schmitt, Fernando
Abstract : Cadherin-catenin adhesion complexes play important roles by providing cell-cell adhesion and communication in different organ systems. Abnormal expression of cadherin adhesion molecules constitutes a common phenomenon in canine mammary cancer and has been frequently implicated in tumour progression. This paper summarizes the current knowledge on cadherin/catenin adhesion molecules (E-cadherin, β -catenin, and P-cadherin) in canine mammary cancer, focusing on the putative biological functions and clinical significance of these molecules in this disease. This paper highlights the need for further research studies in this setting in order to elucidate the role of these adhesion molecules during tumour progression and metastasis.